P‐206: Late‐News‐Poster: Lattice Patterned Micro Lens Array (MLA) Optical Films for Mini‐LED Back Light Units (BLUs). Issue 1 (25th September 2020) - Shen, Bing; Aspell, Jennifer; Rinehart, Thomas; Patel, Katie; Pope, Matthew; Walker, Kenneth
Abstract : A spatially modulated, direct‐lit back light unit (BLU), also known as mini‐LED BLU, is becoming a preferred solution for a high dynamic range (HDR) LCD based display system. With localized dimming, an LCD based display can offer contrast characteristics that are similar to an emissive display system such as OLED. A major challenge facing mini‐LED BLU film stack design, is transforming the grid emission pattern of a mini‐LED array into a uniform luminance area light source. This is particularly true for mobile devices where BLU thickness, or optical distance (OD), must be minimized. We have demonstrated Micro‐Lens Array (MLA) solutions that efficiently eliminate hot spots induced by a mini‐LED array within extremely short OD. Films with various optical structures were analyzed and used to create a high‐performance optical layer within the mini‐LED BLU film stack. To further enhance performance, we propose and demonstrate the concept of a spatially modified MLA optical film with a "lattice" pattern matching the mini‐LED array. Lattice optical films were designed and fabricated at Bright View Technologies and substantial performance enhancements were experimentally demonstrated.